Power & impact : emotional intelligence - Yen, Jonathan; Kaye, Randye (Gildan Audio, 2019)
Gaining power can help you influence others and bring about change. But the misuse of power, especially as a leader, can lead to mistrust, corruption, and abusive behavior. How do you strike the right balance to have the greatest positive impact' This book explains how wielding power affects your emotions and decision making and helps you avoid the traps that lead to negative consequences. With the latest psychological research and practical advice from leading experts, you'll learn how to use soft power to persuade others, fix unhealthy power dynamics in your team, use compassion to connect better with others, and remain ethical in your choices and actions. How to be human at work. HBR's Emotional Intelligence series features smart, essential commentary on the human side of professional life from the pages of Harvard Business Review. Each book in the series offers proven research showing how our emotions impact our work lives, practical advice for managing difficult people and situations, and inspiring essays on what it means to tend to our emotional well-being at work. Uplifting and practical, these books describe the social skills that are critical for ambitious professionals to master.